2021
DOI: 10.1177/09720634211011695
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Encountered by Healthcare Providers in COVID-19 Times: An Exploratory Study

Abstract: Healthcare establishments are unique and complex. The Indian healthcare system comprises of public and private healthcare establishments. Different challenges are encountered by the healthcare professionals in their daily operations. The sudden emergence of COVID-19 posed a new threat to the already burdened healthcare system. The pandemic changed the healthcare paradox with newer workplace and societal challenges faced by the healthcare personnel. The purpose of this study is to identify the antecedents of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…The findings of this study also indicate that there was inadequacy of PPE in hospitals in Vhembe district and in some instances, there was re-use of PPE. Similar findings were noted elsewhere where it was established that supply chains for personal protective equipment were disrupted, resulting in the need for its reuse [ 53 , 54 ]. Other studies that have examined PPE access during the COVID-19 pandemic also found insufficient supplies in different health settings [ 55 , 56 ].…”
Section: Discussionsupporting
confidence: 81%
“…The findings of this study also indicate that there was inadequacy of PPE in hospitals in Vhembe district and in some instances, there was re-use of PPE. Similar findings were noted elsewhere where it was established that supply chains for personal protective equipment were disrupted, resulting in the need for its reuse [ 53 , 54 ]. Other studies that have examined PPE access during the COVID-19 pandemic also found insufficient supplies in different health settings [ 55 , 56 ].…”
Section: Discussionsupporting
confidence: 81%
“…Like other emerging infections [ 32 ], controlling the spread of COVID-19 has been a big challenge to many countries of the world [ 33 35 ]. Thus, even with preparedness and prevention measures instituted, COVID-19 infection spread beyond Wuhan City and China [ 36 ].…”
Section: Epidemiology Of Covid-19 In Africa: Why Is Covid-19 Incidenc...mentioning
confidence: 99%
“…According to recent studies, healthcare providers who directly contact COVID-19 patients have experienced frustration, stress, burnout, and reduced resilience [ 17 ]. Lai et al (2020) report that healthcare professionals who provide care to COVID -19 patients experience higher levels of anxiety and depression and have problems performing their professional duties and their family responsibilities and daily activities [ 18 ].…”
Section: Introductionmentioning
confidence: 99%